DETERMINATION OF PHYSICAL AND MECHANICAL PROPERTIES OF FUZZY COTTONSEED (CAHIERS MAGELLANES-NS, 2024)
The article presents the results of an experimental study of the physical and mechanical properties of fuzzy seed, which has a unique character. Moisture content, main geometrical parameters, bulk and true density, projection surface and necessary non-mechanical properties in the design of the seed feeder device were determined for five types of seed varieties.